Antioxidant Activity and Oxidative Stress Survival of Limosilactobacillus reuteri LR92 in Fermented Milk with Juçara Pulp - Maria Thereza Carlos Fernandes; Fernanda Silva Farinazzo; Carolina Saori Ishii Mauro; Thais de Souza Rocha; Karla Bigetti Guergoletto; Sandra Garcia (Dairy)
Fermented milk with probiotic bacteria is a functional food, and adding fruit can enhance its taste. Juçara, the fruit of the Euterpe edulis Martius palm tree, is known for its natural antioxidant properties. This study aimed to assess the antioxidant capacity of milk fermented by Limosilactobacillus reuteri LR92 with juçara pulp (JFM) over 30 days of storage at 4 °C and its protective effect on probiotic cells against reactive oxygen species (ROS). Phenolic compounds and antioxidant activities were measured using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric-reducing antioxidant power (FRAP) assays during storage. The resistance of L. reuteri to hydrogen peroxide, superoxide anions, and hydroxyl radicals was also tested. The results indicated that JFM maintained stability in its composition, except for color, which showed reduced brightness by the end of the 30 days. Although antioxidant activity measured by DPPH and FRAP decreased (83.92–67.03 µmol TEAC.g−1 and 1185.64–830 g TEAC.100 g.mL−1, respectively), it remained higher than the control (21.90–24.50 µmol TEAC.g−1 and 235.77–229.87 g TEAC.100 g.mL−1, respectively). Phenolic content remained consistent. In addition, juçara pulp significantly protected L. reuteri cells from ROS. Therefore, juçara-enriched fermented milk not only improved antioxidant properties but also shielded probiotics from oxidative stress, highlighting its potential as a functional food with added health benefits.